A high-throughput lipidomics and transcriptomic approach reveals novel compounds from sugarcane linked with promising therapeutic potential against COVID-19 - Rao, Muhammad Junaid; Tahir ul Qamar, Muhammad; Wang, Dongxin; Ali, Qurban; Ma, Li; Han, Shijian; Duan, Mingzheng; Hu, Lihua; Wang, Lingqiang (Frontiers in Nutrition, 2022)
Sugarcane (Saccharum ssp., Poaceae) provides enormous metabolites such as sugars, lipid, and other dietary metabolites to humans. Among them, lipids are important metabolites that perform various functions and have promising pharmacological value. However, in sugarcane, few studies are focusing on lipidomics and few lipid compounds were reported, and their pharmacological values are not explored yet. The transcriptomic and widely targeted lipidomics approach quantified 134 lipid compounds from the rind of six sugarcane genotypes. These lipid compounds include 57 fatty acids, 30 lysophosphatidylcholines, 23 glycerol esters, 21 lysophosphatidylethanolamines, 2 phosphatidylcholines, and 1 sphingolipid. Among them, 119 compounds were first time reported in sugarcane rind. Seventeen lipids compounds including 12 fatty acids, 2 glycerol lipids, LysoPC 16:0, LysoPE 16:0, and choline alfoscerate were abundantly found in the rind of sugarcane genotypes. From metabolic and transcriptomic results, we have developed a comprehensive lipid metabolic pathway and highlighted key genes that are differentially expressed in sugarcane. Several genes associated with α-linolenic acid and linoleic acid biosynthesis pathways were highly expressed in the rind of the ROC22 genotype. ROC22 has a high level of α-linolenic acid (an essential fatty acid) followed by ROC16. Moreover, we have explored pharmacological values of lipid compounds and found that the 2-linoleoylglycerol and gingerglycolipid C have strong binding interactions with 3CLpro of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) and these compounds can be utilized against SARS-CoV-2 as therapeutic agents. The transcriptome, metabolome, and bioinformatics analysis suggests that the sugarcane cultivars have a diversity of lipid compounds having promising therapeutic potential, and exploring the lipid metabolism will help to know more compounds that have promising cosmetic and pharmacological value.